Elderly Patients in the Intensive Care Unit - Flaatten, Hans; Beil, Michael; Guidet, Bertrand (Seminars in Respiratory and Critical Care Medicine, 2020)
Very old intensive care unit (ICU) patients, aged ≥ 80 years, are by no mean newcomers, but during the last decades their impact on ICU admissions has grown in parallel with the increase in the number of elderly persons in the community. Hence, from being a “rarity,” they have now become common and constitute one of the largest subgroups within intensive care, and may easily be the largest group in 20 years and make up 30 to 40% of all ICU admissions. Obviously, they are not admitted because they are old but because they are with various diseases and problems like any other ICU patient. However, their age and the presence of common geriatric syndromes such as frailty, cognitive decline, reduced activity of daily life, and several comorbid conditions makes this group particularly challenging, with a high mortality rate. In this review, we will highlight aspects of current and future epidemiology and current knowledge on outcomes, and describe the effects of the aforementioned geriatric syndromes. The major challenge for the coming decades will be the question of whom to treat and the quest for better triage criteria not based on age alone. Challenges with the level of care during the ICU stay will also be discussed. A stronger relationship with geriatricians should be promoted to create a better and more holistic care and aftercare for survivors.
Keywords: intensive care; critical care; very old; epidemiology; outcomes